Features of the individual teacher of technical disciplines in higher educational establishments - Kuleshova, V.; Malovana, V. (Problems of Engineer-Pedagogical Education, 2018)
Authors in article pay attention to the identity of technical disciplines teacher. It is claimed that specifics of many professions leave a mark to the expert, including in addition some immanent properties of the personality which are defined by features of a profession. In certain cases the health level, resistance to stresses and so on are specified. It is allocated fuller set of personal qualities of technical disciplines teacher as creative person with social and professional significant characteristics. Personal potential of the expert is characterized. It is allocated structure of the expert. The considerable attention is paid for the professional personal development of the expert (pre-university, high school and postgraduate stages). V. Kuleshova, V. Malevanaya note that the identity of technical disciplines teacher is formed, developed, self-actualized, improve in professional activity and like as an active subject of this activity changes himself and his activity. It is revealed that the main resulting effect of professional and pedagogical preparation and retraining of technical disciplines teachers in system of postgraduate engineering pedagogical education is the key of competences formation which allowing it to perform professional functions with the basis of the available knowledge.